A technician's hands operating a Beckman Automatic Amino Acid Analyzer
First marketed in 1960, the Beckman/Spinco Model 120 Amino Acid Analyzer allowed users to quickly perform amino acid chromatography. This later instrument was likely part of the same line and was designed to read the print-outs of other Spinco Amino Analyzers.
Keywords: Medical laboratories--Equipment and supplies; Beckman Instruments, Inc. Spinco Division; Scientific apparatus and instruments; Amino acids--Analysis; Beckman Instruments, Inc.